Surgeons in the emancipation of Peru - Lastres, Juan B. (1952)
Aboriginal surgery had preserved its rich tradition in the early viceroyalty. The Sirkak and Tullu-camayoc, were skilled in managing bone fractures and trying to open holes in the skull. They happened to them the Spanish sixteenth century surgeon, who had learned in Salamanca, Cordoba, Valencia and Alcalá de Henares.